Peningkatan Efisiensi Variabel-Variabel Kritis pada Unit Gawat Darurat dengan Pendekatan Data Envelopment Analysis - Hari Supriyanto (Jurnal Teknik Industri, 2007)
Health represent essential requirement these days. For that on duty in charge have to have yardstick to know efficiency ;level and health service productivity. Measurement of efficiency as productivity index must be done objectively, so that result of measurement can be made input to progress of health of society. Target of research was to make a model assessment of efficiency in order to determination of productivity every health service and determine repair plan to inefficient service. Problem solving used Data model of Envelopment Analysis (DEA) approach. DEA was used to measure productivity and efficiency with input multi and of multi output. With existence of real correct measurement - objective correctness, expected will give instrument to Health department to give satisfaction to wide [of] society. From result of data processing, will be obtained value of technical efficiency for the each Decision Making Unit (DMU) was less efficient, and some repair goals which must reach. Stipulating of peer of group to less efficient DMU will give direction to repair program.